Expression of toll-like receptor 4 and its connection with type 2 diabetes mellitus - Taha, Inass Mohamed; Abdu Allah, Azza M; Abd El Gayed, Eman Masoud (Cellular and Molecular Biology, 2018)
Toll-like receptor 4 (TLR4) plays an important role in modulating innate immunity. Type 2 diabetes mellitus (T2DM) is a chronic disease that is characterized by impaired insulin resistance and abnormal immune response. Genetic background and consequently genetic factors might have a key role in both onset and progression of T2DM-related complications. The aim of this work was to study the role of toll-like receptor 4 (TLR4) in the development of type 2 diabetes mellitus (T2DM). This study was carried out on 90 subjects, 30 type 2 diabetic patients, 30 patients with impaired glucose tolerance and 30 age and gender matched healthy controls. mRNA expression of (TLR4) was assessed by reverse transcriptase PCR (RT-PCR) using real time PCR.. Results showed significant statistical difference between the three studied groups regarding BMI, serum FBG, HDL, TGs, TC, LDL, HOMA -IR and mRNA expression of TLR4 with highest level of TLR4 mRNA expression in T2DM patients. From this study, it might be concluded that high expression of (TLR4) is associated with T2DM.